2015
DOI: 10.1136/bmjspcare-2010-000001rep
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the transition from curative care to palliative care: a systematic review of the literature

Abstract: Background: UK policy guidance on treatment and care towards the end of life identifies a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Identification is only the first step in addressing the multiple, complex barriers that hinder successful introduction of earlier palliative care in acute hospital settings 12 16. Primary care clinicians have said they prefer an individualised, needs-driven approach to introducing palliative care, and often use triggers such as poorly controlled pain or a requirement for increased support from the multidisciplinary team 29 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification is only the first step in addressing the multiple, complex barriers that hinder successful introduction of earlier palliative care in acute hospital settings 12 16. Primary care clinicians have said they prefer an individualised, needs-driven approach to introducing palliative care, and often use triggers such as poorly controlled pain or a requirement for increased support from the multidisciplinary team 29 34.…”
Section: Discussionmentioning
confidence: 99%
“…Linking identification of patients for supportive and palliative care with estimates of prognosis means that clinicians tend to focus on when to start ‘planning for dying’ and may delay a review of care goals and unmet needs until the last weeks of life 16. Earlier identification requires a change from estimating when a patient may die to identifying those who are at sufficient risk of deteriorating and dying for proactive assessment and care planning to be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…While 23% of the inpatient population were identified as having palliative care needs, there was a lack of concurrence between medical and nursing staff regarding which patients had palliative care needs 5. A recent systematic review identified a lack of validated criteria for identifying patients who would benefit from a transition to a palliative care approach, and highlighted that inconsistencies in the identification of patients with palliative care needs may have a negative impact on care delivery 6. There are significant implications of a lack of consensus in identifying which patients have palliative care needs.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than seeking to review the benefits of ICT systems and the quality of their effectiveness on implementation, this paper seeks to outline their structure. Palliative care has been acknowledged as posing its own specific challenges to systematic review methods, with an evidence base largely unsuitable for traditional forms of review and synthesis 13. The approach taken by the current review is to better understand the types of available systems through a descriptive analysis, rather than providing an assessment of the levels of quality or bias of available evidence.…”
Section: Introductionmentioning
confidence: 99%